Determinants of vegetable women farmers’ economic security in Boke region, Guinea (2021)
Vegetable production had been a major source of livelihood among women in Guinea. This study therefore, assessed the determinants of vegetable women farmers’ economic security in the Boke region of Guinea. A multi-stage sampling procedure was used to select 180 respondents for the study. Data was elicited from the respondents with the aid of interview schedule and analysed using descriptive and inferential statistics. The results revealed that average household and farm size cultivated respectively were 8.54±3.55 persons and 1.17±0.62 ha. Personal land (71.7%), household (97.2%) and hired labourers (84.4%) were used by respondents. Almost all (95.0%) relied on personal savings for the finance of vegetable farming. Prominent constraints against vegetable production were inability to access credit at banks (x̅=1.87), lack of storage (x̅=1.87) and processing (x̅=1.86) facility. Vegetable enterprise was not profitable for 53.3% of respondents. Income from vegetable farming was neither adequate (99.4%) nor stable (100.0%). Average annual expenditure ($4,664.92±1723.75) was higher than annual income ($704.49±1,379.98) Almost all the respondents were economically insecure (98.9%) thus unsustainable livelihood and inability to cope with emergencies. Significant predictors of economic security among respondents were household size(β=-0.229), use of personal land (β=-0.188), use of rented or lease land (β=-0.205), use of family land (β=-0.142), use of family/ hired labour (β=0.159), annual income (vegetable) (β=0.596) and the number of vegetables grown (β =-0.150). The study recommends that farmers be encouraged to form cooperatives in order to facilitate access to credit facilities, need for the establishment of cottage industries and promotion of value addition.